The Implementation of Affective Assessment in Islamic Religious Education at Elementary Schools: Between Concept, Practice, and Challenges - Ananda Indriani; Saepul Anwar; Nurti Budiyanti (UIN Sultan Aji Muhammad Idris Samarinda, 2025)
Abstrak Evaluasi pembelajaran pada ranah afektif memiliki peran penting dalam mendukung pembentukan karakter siswa sekolah dasar. Penelitian ini bertujuan mengeksplorasi implementasi asesmen afektif dalam pembelajaran Pendidikan Agama Islam (PAI) di salah satu SDN di Kota Bandung. Metode penelitian yang digunakan adalah kualitatif dengan desain studi kasus melalui wawancara, observasi, dan analisis dokumen. Data dianalisis melalui tahapan reduksi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa guru memahami asesmen afektif sebagai penilaian terhadap sikap, keterlibatan, dan perilaku siswa, namun praktik dokumentasi masih terbatas dan lebih banyak dilakukan secara lisan. Perencanaan dan strategi asesmen bervariasi dengan menggabungkan teknik tradisional, keteladanan, serta rutinitas religius, tetapi penggunaan instrumen formal belum konsisten. Oleh karena itu, penelitian ini menawarkan rancangan sederhana instrumen asesmen afektif yang adaptif untuk sekolah dasar. Temuan ini menegaskan perlunya penguatan kapasitas guru, konsistensi penggunaan instrumen, serta dukungan kebijakan agar asesmen afektif dapat berfungsi optimal dalam pembinaan karakter siswa. Kata kunci: Asesmen, Afektif, PAI, Evaluasi. Abstract The evaluation of learning in the affective domain plays a crucial role in supporting the character formation of elementary school students. This study aims to explore the implementation of affective assessment in Islamic Religious Education (IRE) learning at a public elementary school in Bandung. The research employed a qualitative approach with a case study design through interviews, observations, and document analysis. Data were analyzed through the stages of reduction, presentation, and conclusion drawing. The findings indicate that teachers understand affective assessment as an evaluation of students’ attitudes, engagement, and behavior; however, documentation practices remain limited and are predominantly conducted orally. Planning and assessment strategies vary, combining traditional techniques, role modeling, and religious routines, yet the use of formal instruments has not been consistent. Therefore, this study proposes a simple and adaptive affective assessment instrument for elementary schools. These findings underscore the need to strengthen teacher capacity, ensure consistent use of instruments, and provide policy support so that affective assessment can function optimally in fostering students’ character development. Keywords: Assessment, Affective, Islamic Religious Education (IRE), Evaluation.